Morphological, rheological and electrical properties of composites filled with carbon nanotubes functionalized with 1-pyrenebutyric acid. (15th August 2018) - Guadagno, L.; Raimondo, M.; Vertuccio, L.; Naddeo, C.; Barra, G.; Longo, P.; Lamberti, P.; Spinelli, G.; Nobile, M.R.
Abstract: Non-covalent functionalization of Multi Wall Carbon Nanotubes (MWCNTs) could provide a solution for preserving their electronic structure facilitating the nanocomposite process preparation. Functionalization of MWCNTs by π-stacking interaction between nanofiller and a pyrene derivative has been explored. The rheological properties of filled epoxy resins highlight very interesting benefits from this kind of functionalization. Besides its peculiar capability for preventing agglomeration in the nanofiller dispersion step, it also efficiently contributes to a decrease in the viscosity of the nanocomposites; hence contrasting one of the most relevant drawback related to the manufacturing processes of the nanocomposites at MWCNTs loading rates beyond the Electrical Percolation Threshold (EPT). Because no damage of MWCNTs occurs, sp 2 hybridization of carbon atoms is preserved together with the π-electron delocalization typical of polynuclear aromatic rings. Consequently, no deterioration in the electrical properties are detected; the measured EPT values are typical of nanocomposites containing embedded unfunctionalized MWCNTs (lower than 0.28 wt%), whereas for the electrical conductivity beyond the EPT, an enhancement is observed.